Functional Implications of RFRP-3 in the Central Control of Daily and Seasonal Rhythms in Reproduction - Angelopoulou, Eleni; Quignon, Clarisse; Kriegsfeld, Lance J.; Simonneaux, Valérie (Frontiers in Endocrinology, 2019)
Adaptation of reproductive activity to environmental changes is pivotal to ensure breeding success and offspring survival. In mammals, the reproductive system displays regular cycles of activation and inactivation which are synchronized with seasonal and daily rhythms in environmental factors, notably light intensity and duration. Thus, most species adapt their breeding activity along the year to ensure that birth and weaning of the offspring occur at a time when temperature and food resources are optimal. Additionally, female reproductive activity is highest at the beginning of the active phase during the period of full oocyte maturation, in order to improve breeding success. In reproductive physiology, it is therefore fundamental to delineate how geophysical signals are integrated in the hypothalamo-pituitary-gonadal axis notably by the neurons expressing gonadotropin releasing hormone (GnRH). Several neurochemicals have been reported to regulate GnRH neuronal activity, but recently two hypothalamic neuropeptides belonging to the superfamily of (Arg)(Phe)-amide peptides, RFRP-3 and kisspeptin, have emerged as critical for the integration of environmental cues within the reproductive system. The objective of this review is to summarize the current knowledge on the role of RFRP-3 in the daily and seasonal regulation of reproduction, and consider how its effect might combine with that of kisspeptin to improve the synchronization of reproduction to environmental challenges.